IMF Staff papers : Volume 38 No. 3. (IMF Staff Papers; IMF Staff Papers, 1991)
Trade liberalization in developing countries is frequently opposed on the grounds that, because it is likely to cause a deterioration in the external balance, it may not be a viable policy option for countries facing foreign exchange constraints. Recent literature suggests, however, an ambiguous relationship between tariff changes and the current account. This paper shows that if liberalization involves reducing tariffs on imported intermediate inputs (a reform that has figured prominently in developing countries), then the current account may improve or deteriorate, depending on the level of initial trade distortions and the structure of the economy.[JEL F13, F32, F41].